2009
DOI: 10.1021/ja903694d
|View full text |Cite
|
Sign up to set email alerts
|

Designing 3-D Molecular Stars

Abstract: We have explored in detail the potential energy surfaces of the Si(5)Li(n)(5-6) (n = 5-7) systems. We found that it is feasible to design three-dimensional star-like silicon structures using the appropriate ligands. The global minimum structure for Si(5)Li(7)(+) has a perfect seven-peak star-like structure. The title compounds comprise, essentially, the Si(5)(6-) ring interacting with lithium cations. The ionic character of the Si-Li interactions induces the formation of a bridged structure. Concomitantly, our… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
80
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 81 publications
(88 citation statements)
references
References 61 publications
7
80
1
Order By: Relevance
“…However, they are just local minima on their corresponding PES, 20,24 and therefore impractical targets for experimental detection. We have theoretically designed a stable silicon-based C 5 H 5 analogue: the Li 7 Si 5 + (D 5h ) cluster, which is a star-like molecule in its lowest energy conformation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, they are just local minima on their corresponding PES, 20,24 and therefore impractical targets for experimental detection. We have theoretically designed a stable silicon-based C 5 H 5 analogue: the Li 7 Si 5 + (D 5h ) cluster, which is a star-like molecule in its lowest energy conformation.…”
Section: Introductionmentioning
confidence: 99%
“…We have theoretically designed a stable silicon-based C 5 H 5 analogue: the Li 7 Si 5 + (D 5h ) cluster, which is a star-like molecule in its lowest energy conformation. 20 Subsequently, it has unequivocally been shown that the five-pointed star shape is a common structural pattern for minimum energy conformation of Li 7 E 5 + (E = C, Si, and Ge). 25,26 This unusual high-symmetry pattern is favored by i) the aromaticity in the central fivemembered ring, and by ii) the preference by Li atoms for bridging positions.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, cluster design based on chemical bonding already has successful precedents Galeev et al 2012;Tiznado et al 2009;Zhang and Alexandrova 2013). We, as a community, are in the privileged position to write a new textbook chapter on the chemistry of clusters.…”
Section: Introductionmentioning
confidence: 99%
“…27 Interestingly, the multi-lithium doped silicon cluster Si 5 Li 7 was predicted to have a perfect seven-peak star-like structure due to the electron donation behavior of the Li atoms. 28 Some experimental data on sodium doped silicon clusters, including threshold photoionization and photoelectron spectroscopy studies, are available. [29][30][31][32] However, not many experiments are reported for the lithium congener.…”
Section: Introductionmentioning
confidence: 99%